Застосування методу теорії систем щодо аналізу електричних пристроїв - Бондар, О. Д. (ХНУРЕ, 2020)
The increasing complexity of processes and events m science, technology and other fields of activity is the ever-expanding use of mathematical and computational methods. In connection with these circumstances, the concept of “system” is enriched in content and acquires quantitative characteristics. The concepts of complex and large systems, systems engineering, systems theory, systems approach are widely used. Traditional scientific directions and educational disciplines are influenced by the theory of systems and systems approach, terminological and mathematical apparatus.Here we consider an example of applying a systematic approach to the analysis of electrical devices